Industrial-organizational psychology society honors Professor Olson-Buchanan - Fresno State::::::::: (2013)
Dr. Julie B. Olson-Buchanan, professor and chair of the Department of Management in Fresno State's Craig School of Business, has been elected a fellow of the Society for Industrial and Organizational Psychology.